The Eighth Workshop on Reindeer Research 1994 - Haugerud (ed.), Rolf Egil (Rangifer, 1995)
The workshop was held at Kaamanen, Finnish Lapland, in connection with the opening of the new Reindeer Research Station. There were about 70 participants discussing EU and reindeer husbandry.